The Brand Personality: a Key Catalyst of the Consumer-brand Relationship - Trabelsi, Maryem (American Journal of Trade and Policy, 2019)
In our post-modern era, the brand is perceived more than a simple means of identification of the producer and a tool of differentiation and distinctiveness. From the consumer’s angle, it is seen as a partner in a deep, affective and long-lasting relationship that reflects his personality, values, social status, ideology, world view to match with this new perception, managers should infuse their brands with distinctive traits that match with the current and potential customers’ needs and identification desire. This research goes in this stream of studies that focus on brand personality and its ability to create, develop and maintain a strong consumer-brand tie. The findings showed that Private Labels’ personality is capabe enough to generate trust and attachment in the Tunisian context.
Keywords: brand personality; consumer-brand relationship; brand attachment; brand trust; Private Labels